A Review on Some Chemical Engineering and Microbiological Aspects Considered in the Production of Highly Concentrated Probiotic Cultures and Bacteriocins by Lactococci and Lactobacilli. (25th December 2012) - Guerra, Nelson Pérez
Abstract : The main purpose of this work is to give an overview on the chemical engineering aspects related with the production of probiotic cultures and bacteriocins. Firstly, some evidence of the potential of different Lactococci and Lactobacilli strains for prevention or treatment of different human diseases, or as growth promoters in farm animals is given. In addition, examples of different commercial dietary supplements containing probiotic lactoccocci and lactobacilli in combination or not with other probiotic bacteria are presented. Secondly, the main factors (cultivation method, culture media, and media composition) affecting the production of bacteriocins by lactoccocci and lactobacilli strains are showed. Examples of modelling procedures developed to describe the production of higher concentrations of biomass and bacteriocins in fed-batch cultures subjected or not to successive alkalizations are summarized. Finally, the corresponding mass balance equations performed in the latter cultures are presented to calculate the volumes of feeding substrates and the concentrations of nutrients (lactose, glucose, proteins, nitrogen, and phosphorous) added to the fermentation medium, as well as the concentrations of biomass and products in the fermentor just after each feeding.